Risk factors for long-term complications in patients with type 2 diabetes, in Sri Lanka - D. A. C. L. Amarasinghe; P. Fonseka; D. J. S. Fernando; K. C. S. Dalpatadu (College of Community Physicians of Sri Lanka, 2004)
Objective: To identify risk factors for long term complicatio os in patients with type 2 diabetes in Sri Lanka.   Methodology: An unmatched, clinic- based, case control study. Diabetic patients enrolled from randomly selected medical clinics from primary, secondary and tertiary care level hospitals were interviewed to determine possible risk factors and· screened for long term complications. 252 diabetic patients having one or more Jong term complications were selected as cases and 288 diabetic patients free from long term complications included as controls.   Results: Peripheral diabetic neuropathy (25.2%), micro albuminuria (22.8%), retinopathy (20%), and coronary heart disease (12.4%) were some complications present among cases. 21.9% had only one complication while 16.5% and 6.9% had two and three com plications respectively. Only 1.5% had au fourcomplications.   In the univariate analysis, smoking, low family income, body mass index over 25, older age (over 60 years), longer duration of diabetes (11 -15 years), random blood sugar > 11, 0mmoV/, raised diastolic blood pressure > 90mmHg were significantly (p<0.05) associated with the development of long-term complications, The latter four factors were significantly associated with a number of complications. Multivariate analysis identified older age (OR = 5. 51 CI 1.59, 19.17), duration of diabetes (OR= 2.08CI 1.23, 3.50), random blood sugar 11.0-16.7 mmol/l (OR= 3.15 CL 1.31, 7.56) and current smoking (OR= 8.88, CI 1.53, 51.53) as significant risk factors.   Conclusion: Long-term complications in type 2 diabetes are common among patients. Most of the significant risk factors are preventable.